2019
DOI: 10.1155/2019/7606238
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid Methyl Ester Induces G2/M Arrest in Human Bone Marrow-Derived Mesenchymal Stem Cells via the p53/p21 Pathway

Abstract: Bone marrow-derived mesenchymal cells (BM-MSCs) are able to differentiate into adipocytes, which can secrete adipokines to affect BM-MSC proliferation and differentiation. Recent evidences indicated that adipocytes can secrete fatty acid metabolites, such as palmitic acid methyl ester (PAME), which is able to cause vasorelaxation and exerts anti-inflammatory effects. However, effects of PAME on BM-MSC proliferation remain unclear. The aim of this study was to investigate the effect of PAME on human BM-MSC (hBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…MP has induced Peroxisome proliferator‐activated receptor gamma‐α (PPAR‐α) expression for its preventive action on steatohepatitis 68 and the PPAR‐α expression is high in certain organs which are having high level of fatty acid metabolism. MP was found to induce G2/M arrest via p53/p21 pathway 69 and proven to have anti‐inflammatory activity in experimental rat 70 . MP has protected peritoneal cells from toxicity induced in rat by Lipopolysacharide (LPS) by inhibiting the enhanced macrophages 71 .…”
Section: Discussionmentioning
confidence: 99%
“…MP has induced Peroxisome proliferator‐activated receptor gamma‐α (PPAR‐α) expression for its preventive action on steatohepatitis 68 and the PPAR‐α expression is high in certain organs which are having high level of fatty acid metabolism. MP was found to induce G2/M arrest via p53/p21 pathway 69 and proven to have anti‐inflammatory activity in experimental rat 70 . MP has protected peritoneal cells from toxicity induced in rat by Lipopolysacharide (LPS) by inhibiting the enhanced macrophages 71 .…”
Section: Discussionmentioning
confidence: 99%
“…The Cdk1/cyclin B1 complex is a crucial initiator of mitosis, and has been reported to coordinate G 2 /M progression (34). Studies have revealed that activation of this complex can be blocked by upregulating p21 (34,35). In the present study, neferine suppressed proliferation of tumor cells, by blocking cell cycle progression, although the mechanisms underlying this phenomenon are unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, it was observed that neferine treatment increased the G 2 /M phase in ESCC cells by downregulating the expression of cyclin B1 while upregulating that of p21. The Cdk1/cyclin B1 complex is a crucial initiator of mitosis, and has been reported to coordinate G 2 /M progression (34). Studies have revealed that activation of this complex can be blocked by upregulating p21 (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that PAME was synthesized through PA methylation via the AdoMet-dependent catechol-O-methyltransferase catalytic pathway in adipocytes [ 37 ]. Recently, we detected PAME in the rat bone marrow [ 25 ]. Lee et al reported that the culture medium of differentiated adipocytes of NIH 3T3 and 3T3-L1 cells contained a significant concentration of PAME [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAME has been shown to inhibit phagocytosis [ 38 , 39 ], fibrotic effects [ 18 20 ], inflammation [ 21 , 22 ], and oxidative stress [ 40 ]; to induce vasodilation [ 17 , 35 , 36 , 41 , 42 ]; and to prevent nonalcoholic steatohepatitis [ 43 ]. In stem cells, PAME is able to induce cell cycle arrest at the G 2 /M phase in hBM-MSCs [ 25 ]. However, the molecular mechanisms underlying PAME-induced stem cell differentiation are still unclear.…”
Section: Discussionmentioning
confidence: 99%